2014
DOI: 10.7314/apjcp.2014.15.14.5611
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Tobacco Control in Masters of Public Health Curricula of India

Abstract: Context: Tobacco is the single largest cause of preventable death among adults globally, as it is in India. Despite this alarming situation, there is very minimal inclusion of tobacco in formal education systems, including the medical discipline, in India. Aims: The present study analyzed the extent of integration of tobacco control related content in Masters of Public Health (MPH) curricula of various institutes in India. Materials and Methods: This cross-sectional study was conducted during January 2011 to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Comparing the data with nationwide statistics, participants exercised 48% and used dental floss 39% less often than the general population (Yadav et al, 2014). A alcohol, betel nut and cigarette consumers also think vegetable and fruit eating were significantly less OR-3.4 and took less exercise (14.5%) than those without these 2 habits (Table 1).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparing the data with nationwide statistics, participants exercised 48% and used dental floss 39% less often than the general population (Yadav et al, 2014). A alcohol, betel nut and cigarette consumers also think vegetable and fruit eating were significantly less OR-3.4 and took less exercise (14.5%) than those without these 2 habits (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…With the passage of time, there is an ever increasing burden of both communicable and non-communicable diseases in developing countries. As tobacco is emerging as major threat for non-communicable diseases, it is important for public professionals to concentrate on new emerging health issues like tobacco control (Yadav et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The raising of age of purchase of tobacco products at Point of Sale (POS) from existing 18 years to 21 years is also a useful strategy to curb initiation of tobacco products . Further, tobacco control related issues should be integrated in curricula of public health students, so as to build their capacity for influencing policy makers on this key issue (Yadav et al, 2014). Youth are extremely sensitive to price, and if taxes are raised above inflationary trends and strongly administered, tobacco products will become less affordable (World Bank, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that health professionals are willing to participate in tobacco cessation activities (Binnal et al, 2012, Saba et al, 2014, Han et al, 2014. Nevertheless, lack of expertise and administrative barrier has been reported as main barriers in inclusion of tobacco control in the health care professional curriculum (Panda et al, 2013, Yadav et al, 2014.…”
Section: Effectiveness Of Tobacco Education For Pharmacy Students In mentioning
confidence: 99%